PENGARUH INFORMATION OVERLOAD TERHADAP INTENTION TO MAKE UNUSUAL PURCHASES MELALUI PERCEIVED SEVERITY PADA MASYARAKAT KOTA BANDUNG SELAMA PANDEMI COVID-19 - Pramesti, Tiara; Dewi, Citra Kusuma (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS DR SOETOMO SURABAYA, 2021)
The purpose of the study is to determine the influence of information overload on intention to make unusual purchases through perceived severity in the people of Bandung during the COVID-19 pandemic. This study uses quantitative methods with descriptive research types and causality. Sampling uses non probability sampling techniques with purposive sampling method to 100 respondents of Bandung city with a population of 2,510,103.00 people. Analysis of research data using tenik descriptive analysis and path analysis. The conclusion of the study shows variable information overload and perceived severity fall into the category of very high and variable intention to make unusual purchases fall into the high category. In addition, variable information overload had a significant effect on perceived severity of 46.92%. Information overload significantly affects intention to make unusual purchases by 6.25%. Perceived severity significantly affects intention to make unusual purchases by 19.80%. Information overload affects indirectly the intention to make unusual purchases through perceived severity of 30.48%.